Characteristics of top performances in the women's hammer throw: Basics and technique of the world's best athletes - Bartonietz, K.; Barclay, L.; Gathercole, D. (1997)
Starting from a presentation of the biomechanical basics of the hammer throw the author characterizes the performance development, performance structure and the technique of Olga Kuzenkova. who was the leading female hammer thrower in 1996, as in previous years. The analysis shows that the world's best female hammer thrower demonstrates a high level of athletic technique although there is still room for further improvement The main requirements for the men's hammer throw are also valid for the training structure of female athletes, i.e. (1) an increase of the training quality (high level of consciousness, execution of the training exercises corresponding with the demands of the target technique), (2) on optimisation of the effects of the yearly training cycle, by varying the components of the training load with regard to volume and intensity, and (3) a balancing of the training loads with restorative and prophylactic measures.